2007
DOI: 10.1007/s11695-007-9004-7
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey on Bariatric Surgery in France: Two Years Prospective Follow-up

Abstract: Outcomes of bariatric surgery in routine practice (mortality, weight loss, course of co-morbidities, and quality of life) are similar to the results published in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
0
18
0
15
Order By: Relevance
“…Three recent studies, both with restrictive [3,4] and malabsorptive procedures [5], have even demonstrated a significant decrease of mortality several years after bariatric surgery. The two types of procedures, most often performed in Europe, are adjustable gastric banding (AGB), a purely restrictive reversible procedure, and gastric bypass (GBP), an irreversible procedure, which associates restriction and mild malabsorption [6]. GBP seems to be more efficient in terms of weight loss but also for improvement of comorbidities, notably diabetes and dyslipidemia [1,2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Three recent studies, both with restrictive [3,4] and malabsorptive procedures [5], have even demonstrated a significant decrease of mortality several years after bariatric surgery. The two types of procedures, most often performed in Europe, are adjustable gastric banding (AGB), a purely restrictive reversible procedure, and gastric bypass (GBP), an irreversible procedure, which associates restriction and mild malabsorption [6]. GBP seems to be more efficient in terms of weight loss but also for improvement of comorbidities, notably diabetes and dyslipidemia [1,2,7].…”
Section: Introductionmentioning
confidence: 99%
“…The patients were selected to be operated on the established criteria of the National Health Authority (Haute Autorité de Santé) [6].…”
Section: Methodsmentioning
confidence: 99%
“…Parmi les 1 083 patients suivis à un an, 946 ont eu un anneau. Des complications spécifiques à l'anneau ont été observées chez 17 % des patients à un an et chez 22 % à deux ans [2]. Parmi les 876 anneaux suivis avec un recul de deux ans, les complications les plus fréquentes ont été les suivantes : les problèmes de boîtier (6,7 %), une intolé-rance alimentaire (8,1 %) et des douleurs scapulaires (4,6 %).…”
Section: Résultatsunclassified